2023
DOI: 10.1128/iai.00085-23
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichia Wnt SLiM ligand mimic deactivates the Hippo pathway to engage the anti-apoptotic Yap-GLUT1-BCL-xL axis

Caitlan D. Byerly,
LaNisha L. Patterson,
Nicholas A. Pittner
et al.

Abstract: Ehrlichia chaffeensis TRP120 effector has evolved short linear motif (SLiM) ligand mimicry to repurpose multiple evolutionarily conserved cellular signaling pathways, including Wnt, Notch, and Hedgehog. In this investigation, we demonstrate that E. chaffeensis and recombinant TRP120 deactivate Hippo signaling, resulting in the activation of Hippo transcription coactivator Yes-associated protein (Yap). Moreover, a homologous 6 amino acid (QDVASH) SLiM shared by TRP120 and Wnt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…However, ubiquitinated APC was undetectable during mid to late infection when Ehrlichia replication is occurring. One explanation for this observation, is that E. chaffeensis is targeting APC before replication begins, to prevent host-cell apoptosis and is consistent with previous findings that demonstrate E. chaffeensis activates Yap to prevent apoptosis ( Byerly et al, 2023a ). Collectively, these results demonstrate that TRP120 ubiquitinates APC to stabilize active Yap and β-catenin levels in the nucleus to promote infection.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, ubiquitinated APC was undetectable during mid to late infection when Ehrlichia replication is occurring. One explanation for this observation, is that E. chaffeensis is targeting APC before replication begins, to prevent host-cell apoptosis and is consistent with previous findings that demonstrate E. chaffeensis activates Yap to prevent apoptosis ( Byerly et al, 2023a ). Collectively, these results demonstrate that TRP120 ubiquitinates APC to stabilize active Yap and β-catenin levels in the nucleus to promote infection.…”
Section: Discussionsupporting
confidence: 90%
“…E. chaffeensis exploits evolutionarily conserved host cell signaling pathways, including Hippo, Wnt, Notch and Hedgehog to prevent apoptosis and other innate immune defenses for intracellular survival ( Rogan et al, 2021 ; Byerly et al, 2022 ; Patterson et al, 2022 ; Byerly et al, 2023a ). Both Hippo and Wnt are known for their role in regulating cellular proliferation and cell fate ( He et al, 2015 ; Wang et al, 2017 ; Qian et al, 2021 ), and we identified TRP120 as a novel Wnt ligand mimic that activates Yap and β-catenin, preventing apoptosis for ehrlichial survival ( Rogan et al, 2021 ; Byerly et al, 2023a ). Yap and β-catenin activate gene transcription under two conditions; when Hippo signaling is inactivated and APC is degraded ( Cai et al, 2015 ; Park et al, 2015 ; Wang et al, 2017 ; Lee et al, 2018 ; Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations